Thomas & friends. Hop on board [videorecording (DVD)] : songs and stories - Allcroft, Britt; Awdry, W. (Distributed by Lionsgate, 2009)
Life on the Island of Sodor is very busy for the engines. While Thomas and his friends are hard at work, they like to listen to music and sing along. Follow the bouncing steam cloud to read the words and sing along to seven Sodor favorites. So hop on board for toe-tappin' fun with Thomas and his friends.